Nanostructure, self-assembly and friction in confined liquids - Smith, A (2015)
The work presented in this thesis uses a custom-built surface force balance with extreme sensitivity and resolution to understand at the molecular level how the structure of confined liquid films relates to their frictional and lubricating properties. The experiments involve shearing two identical and atomically smooth mica surfaces past one another with sub-nanometer control of the film thickness and ultrasensitive force resolution. With this, molecular mechanistic details relevant to boundary lubrication are uncovered for several systems. Friction modifiers are commonly used in engine oil formulations and adsorb as monolayers to surfaces, preventing surface contact and reducing friction between the surfaces. Here it is shown that the shape of additive surfactant molecules affects both the confined film structure and the lubricating behavior, with more upright monolayers exhibiting lower friction. Interestingly, mixing different surfactant molecules can give rise to friction much higher than for either molecule. This result is significant given that lubricant formulations typically contain many different types of additive molecules with different functions. Measurements made with ionic liquids of varying alkyl chain length reveal a dramatic cross-over in the interfacial layering structure, from alternating cation- and anion-enriched monolayers for ionic liquids with short alkyl chains, to bilayer formation for more amphiphilic ions. Their structural and dynamic properties in confinement are pertinent to applications ranging from electrolytes in nanoporous electrodes to specialist lubricants in extreme environments. The ionic liquids show clear evidence for ‘quantized friction’, where multiple friction-load regimes with different friction coefficients are measured for different numbers of confined ion layers for the same ionic liquid. Most significantly, the results of these experiments allow elucidation of shear mechanisms and sliding interfaces for monolayer and bilayer-forming ionic liquids which differ markedly to those of molecular liquids.